Serum Leptin Is not a Diagnostic Marker for Familial Mediterranean Fever Attacks - Bülent Toy; Orhan Tarçın; Sait Bağcı; Yücel Üstündağ; Ali Inal; Arzu Tiftikçi (Mediators of Inflammation)
The aim of our study is to determine whether there is a relationship between familial Mediterranean fever (FMF) attacks and serum leptin levels. We enrolled 25 patients (22 males and 3 females) and 25 healthy controls (21 males and 4 females) with a mean age of 24.42±1.22 (Mean ± SEM) years and 24.30±1.19 years (Mean ± SEM), respectively. We investigated serum levels of leptin, interleukin-6 (IL-6) erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), fibrinogen, and leukocyte counts before the attack and 8–12 hours after the attack started. The same parameters have been investigated in the control subjects. The mean serum leptin levels before the attacks were 6.45±1.05 (Mean ± SEM) and during the attacks were 7.59±1.3 (Mean ± SEM) in FMF group, respectively. There was a slight increase in serum leptin levels during the attacks but it was not statistically significant (P>.05). The mean serum leptin levels were 6.12±2.81 in the control group which were not different from the mean serum leptin levels before and during the attack periods in the study group (P>.05). However, there were statistical differences in the serum levels of IL-6, ESR, CRP, fibrinogen, and leukocyte counts before and during the attack periods (P<.05). No correlation was found between serum leptin levels and IL-6, ESR, CRP, fibrinogen, and leukocyte counts (P>.05). Serum leptin levels do not increase during FMF attacks and therefore it is not useful for diagnostic purposes and follow-up during treatment.